Hashimoto’s encephalopathy – an up-to-date overview - Szydełko, Joanna; Litwińczuk, Michał; Szydełko, Magdalena (Journal of Education, Health and Sport, 2019)
Introduction: Hashimoto’s encephalopathy (HE) is a rare, potentially life-threatening disease with a wide spectrum of clinical manifestations from slight symptoms to mainly neurological and psychiatric syndromes, which significantly debilitate the quality of life and make the diagnostic process complicated, especially in patients with no previous history of thyroid disorders. According to the recent data, it occurs in about 2.1 cases per 100 000 population with still increasing prevalence. Despite, over than fifty years have passed since the first case of HE was reported, its etiopathogenesis is not completely clarify and there is no universal diagnostic criteria. Aim of the study: This article summarizes the current knowledge about pathophysiology, clinical manifestations, difficulties in differential diagnosis and therapeutic dilemmas in patients with HE. Description of knowledge: HE is an autoimmune-mediated encephalopathy associated with Hashimoto’s disease and elevated titers of anti-thyroid antibodies, mainly anti-thyroid peroxidase antibody. The diagnostic process is usually multi-step due to various diseases mimicking HE, such as Creutzfeldt-Jacob disease, brain tumors, epilepsy, Alzheimer's disease, stroke, other forms of autoimmune encephalitis, schizophrenia, spontaneous cerebrospinal fluid leak or infectious encephalitis. The range of diagnostic procedures includes physical and mental examination, laboratory tests, brain imaging, EEG as well as cerebrospinal fluid analysis. However, the first line strategy based on steroids is effective, there are some cases in the literature that reveal this management as not fully sufficient, because only partial improvement was achieved or the steroid-dependence was observed. Among other therapeutic methods, plasmapheresis may be used additionally. Conclusions: HE requires interdisciplinary approach and it constitutes a great challenge for clinicians of various specialties, such as endocrinologists, neurologists, and psychiatrists. The prompt implementation of adequate therapy usually provides the full recovery of the patients without any early or late complications.